Value-at-Risk Based Portfolio Allocation Using Particle Swarm Optimization - Ray, Jhuma; Bhattacharyya, Siddhartha (International Journal of Computer Sciences and Engineering, 2015)
Risks and returns are inevitably interlinked in today's work-a-day real world financial transactions. In particular, a financial portfolio illustrates the situation in which a combination of financial instruments/assets describes this interrelation in terms of their correlation in a particular market condition. The field of portfolio management has assumed importance of late, thanks to the need for decision making in investment opportunities in a high-risk scenario. It addresses the risk-reward tradeoff allocation of investments to a number of different assets so as to maximize returns or minimize risks in a given investment period. In this paper, a particle swarm optimization procedure is used to evolve optimized portfolio asset allocations in a volatile market condition. The proposed approach is centered around optimizing the Value-at-Risk (VaR) measure in different market conditions based on several objectives and constraints. Applications of the proposed approach are demonstrated on a collection of several financial instruments.